Integrated Community Health Surveillance to Identify Environmental and Behavioral Risk Factors in Rural Indonesia: Evidence from Tounsaru Village - Jonesius Eden Manoppo; Indri Trisalowika Purba; Krisma Gloria Rumondor; Robintang Situmorang; Christin Meyni Suoth; Nesa Mokodompit; Jeckson Wakerkwa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Goal. This study aims to provide a comprehensive analysis of community health conditions in Tounsaru Village through integrated community health surveillance, focusing on environmental health risks, behavioral risk factors, and the growing burden of hypertension. The objective is to generate accurate household-level evidence to support public health planning and targeted intervention strategies. Materials and methods. A community-based surveillance design was implemented in the working area of Puskesmas Koya. Data were collected from 30 randomly selected households through structured interviews and direct field observations. A standardized instrument was used to assess sanitation conditions, environmental health indicators, household behaviors, disease occurrence, and risk exposure. The results showed that hypertension was the most prevalent chronic condition, closely associated with widespread smoking, low routine health monitoring, and limited knowledge of preventive care. Environmental assessments revealed inadequate wastewater disposal, inconsistent solid waste management, and minimal vector-control practices, creating persistent risks for infectious and vector-borne diseases. Although reported cases of diarrhea and respiratory infections were low, underlying environmental vulnerabilities remained significant. Household adherence to clean and healthy living behaviors varied, with notable gaps in hand hygiene and environmental cleanliness. The findings confirm that community health outcomes in rural settings are shaped by a combination of behavioral, environmental, and epidemiological factors. The study demonstrates the value of integrated household surveillance in identifying health risks and informing context-specific interventions. Strengthening hypertension monitoring, sanitation improvements, and vector-control education are essential to enhance community health resilience.